A bipolar modified separator using TiO2 nanosheets anchored on N-doped carbon scaffold for high-performance Li–S batteries. (15th October 2020) - Li, Na; Chen, Fei; Chen, Xiangtao; Chen, Zhongxu; Qi, Yang; Li, Xiaodong; Sun, Xudong
Abstract: Lithium-sulfur batteries hold promise for next generation batteries due to their high theoretical energy density and low cost. However, the rapid capacity fading caused by the shuttle of polysulfide between two electrodes severely hinders the practical application of Li–S batteries. To address the issue, we reported a three-dimensional heterostructured TiO2 nanosheets/N-doped carbon (TO/NC), which is coated on a commercial polypropylene (PP) separator, as an efficient barrier for Li–S batteries. The TO/NC coating layer provides a bipolar chemical adsorption of lithium polysulfides (LiPSs) via TiO2 nanosheets with exposed (001) facets and N-doped carbon, showing high trapping capacity and remarkable electrocatalytic activity for LiPSs. The slurry-bladed carbon black/sulfur cathode with 64 wt% sulfur offers outstanding performance with an initial capacity of 1314 mA h g −1 at 0.2 C. Over 900 cycles, the cell still maintains the capacity of 448 mA h g −1 at a 1 C rate with a degradation rate of only 0.055% per cycle. The separator reported in this work holds great promise for the development of high-energy Li–S batteries.